Analisis Pengaruh Asam Organik dari Cangkang Kelapa dengan Metode Pirolisis Terhadap Proses Reduksi Scale di Industri Minyak - Putri, Aninda Arik Tanza; Meidinariasty, Anerasari; Ekawati, Linda (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Scale problems in the oil industry have become a serious challenge because they can clog piping systems and reduce operational efficiency. This study aims to evaluate the effectiveness of organic acids from coconut shell pyrolysis as an environmentally friendly scale reducer and compare it with HCl solutions at various concentrations. Pyrolysis was carried out at a temperature of 500°C for 30 minutes to produce bio-oil rich in phenolic compounds and organic acids. Characterization using GC-MS showed the dominance of phenol compounds, 2-methoxy phenol, and 2,6-dimethoxy phenol which play an active role in the reduction process. Reduction tests were carried out on Fe₂O₃, Fe₃O₄, and FeSO4-based scales with time variations of 5-40 minutes, and 5-30% HCl as a comparison. The results showed that organic acid was able to reduce scale by up to 36.03% in 40 minutes, equivalent to 15% HCl (37.85% at 20 minutes) and 25% HCl (37.45% at 10 minutes). The optimum effectiveness of organic acid occurred at 30.04% at the 25th minute. Although HCl showed a higher reduction capacity, organic acid was considered safer for the environment and metal infrastructure. This study indicates that bio-oil from coconut shell pyrolysis has potential as a sustainable alternative for scale reduction.